The ESAFORM benchmark 2023: interlaboratory comparison benchmark for the characterization of microstructural grain growth and dynamic recrystallization kinetics of a single-phase Ni-base superalloy - Agirre, Julen; Bernal, Daniel; Flipon, Baptiste; Bernacki, Marc; Brüggemann, Holger; Bailly, David; Merklein, Marion; Hagenah, Hinnerk; Risse, Jan Henning; Madej, Łukasz; Muszka, Krzysztof; Cichocki, Kamil; et al. (International Journal of Material Forming, 2025)
This paper presents an extensive benchmark study conducted across eight European research centres, focusing on the high-temperature testing of the Alloy 625 nickel-based superalloy to evaluate its flow behaviour and microstructural evolution, including grain growth (GG) and dynamic recrystallization (DRX). Uniaxial compression tests were performed at 1050 °C and three strain rates (0.1 s⁻1, 1 s⁻1, and 10 s⁻1) using six testing facilities categorised into three types: two conventional thermomechanical machines equipped with electrical resistance furnaces, two deformation dilatometers with induction heating, and two Gleeble machines with Joule heating. Flow curves were compared, and EBSD analysis was conducted to examine DRX. Virtual twins of tests were developed to estimate the thermomechanical history at the centre of the samples, where microstructural observations were conducted. The study methodically discussed the variability in thermomechanical behaviour and DRX results. Additionally, GG was investigated through heat treatments at 1150ºC for various hold times, using the three heating methods mentioned. Significant effects of the heating methods on GG were identified. In-situ synchrotron analysis at PETRA III DESY provided deeper insights into microstructural evolution. Considering the extensive findings of this research, this paper aims to establish guidelines and define best practices for high-temperature testing to characterise the thermomechanical behaviour and microstructural evolution of materials, while providing insights for advancing experimental mechanics and optimising constitutive model development.
Created from Fastlane, Scopus look-up
Keywords: Benchmark; High temperature testing; Uniaxial compression; Microstructural evolution; Grain growth; Dynamic recrystallization; EBSD analysis; Virtual twins; In-situ testing